The Poetics Of Imagery In The Praise Poems Of Abu Al-Atahiya - Ali Ahmad Al-Momani (Kurdish Studies, 2024)
The artistic image is one of the most important pillars that the poet relies on to express the feelings and ideas within himself, he uses extreme degrees of imagination, which goes beyond all limits, to achieve the intended meaning and produce an artistic image in which the features of modern poetry emerge through the use of words, imagination, and connotation in a linguistic template that holds an abundance of significance. The poetics of the artistic image appear in the use of words and connotations to depict a fictional scene in which the poet exceeds the limits of reality to the world of wild imagination. It became clear to the researcher that the features of poetics were represented in the artistic image of Abu al-Atahiya, which he used in praise poems, as the poet excelled in selecting his artistic images, which carried many connotations that foretell the status and position of the one praised, which is evident in his praise of the Abbasid caliphs al-Mahdi, al-Hadi, and al-Rashid. He transitioned to the world of imagination to select some connotations of praise that existed in his time and mix them into an artistic image in which his poetic ability was highlighted.